2021
DOI: 10.1155/2021/3754922
|View full text |Cite
|
Sign up to set email alerts
|

Stagnation Point Flow of EMHD Micropolar Nanofluid with Mixed Convection and Slip Boundary

Abstract: The aim of this numerical research is to study the stagnation point flow of the electrical magnetohydrodynamic micropolar nanofluid with slip conditions past a stretching sheet. The phenomenon of linear thermal radiation, Ohmic and internal heating, has also been considered in the energy equation. The modelled PDEs are converted into ODEs via similarity transformation, and converted ODEs are tackled via the shooting technique. The features of assorted parameters on the axial and angular velocities and energy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Haroon et al [16] examined the effects of uniform magnetism and heat radiation on nanofluid flow, noting that magnetism impedes fluid flow. Atif et al [17] considered a micropolar-based nanofluid with thermal radiation and mixed convection, finding that magnetic field presence enhances flow temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Haroon et al [16] examined the effects of uniform magnetism and heat radiation on nanofluid flow, noting that magnetism impedes fluid flow. Atif et al [17] considered a micropolar-based nanofluid with thermal radiation and mixed convection, finding that magnetic field presence enhances flow temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Hussain et al 12 examined the micropolar nanofluid via stretching sheets numerically. Following them, Patel et al , 13 Lund et al , 14 Atif et al 15 and numerous others have investigated various surfaces and angles of the micropolar nanofluid flow problem.…”
Section: Introductionmentioning
confidence: 99%
“…Both researchers discovered that increasing the magnetic parameter (M) or electrical parameter (E) results in an increase in temperature distribution at a specific point of the flow region. Furthermore, Shahzada et al [29] also expanded on Hsiao [27] research by looking at the stagnation point flow of an EMHD micropolar nanofluid with mixed convection and slip boundary. Recent studies by Ishak et al [30] and Olanrewaju et al [31] examined the effects of thermal radiation on magnetohydrodynamic (MHD) flow of micropolar fluid towards a stagnation point on a vertical surface and found that thermal radiation and absorption has greater impact on the velocity, angular velocity and temperature field.…”
Section: Introductionmentioning
confidence: 99%